TiO2 nanocomposite for the controlled release of drugs against pathogens causing wound infections. (6th February 2018) - Venkatasubbu, G Devanand; Nagamuthu, S; Anusuya, T; Kumar, J; Chelliah, Ramachandran; Ramakrishnan, Sudha Rani; Antony, Usha; Khan, Imran; Oh, Deog-Hwan
Abstract: Chitosan titanium dioxide nanocomposite has been used for wound healing. Titanium dioxide (TiO2 ) nanoparticles are synthesised and made in to nanocomposite along with chitosan. Curcumin nanoparticles are synthesised. Three different drugs with antimicrobial activity are incorporated into the chitosan/TiO2 nanocomposite. Ciprofloxacin, amoxicillin and curcumin nanoparticles are incorporated within the chitosan/TiO2 nanoparticles. The nanoparticles and nanocomposite are characterized with XRD, FTIR, TEM and SEM. Drug loading was found to be around 45% for all the three drug molecules. The drug release profile shows a controlled release of drug molecules from the nanocomposite. Antibacterial studies shows a good inhibition of bacterial species by the nanocomposites.